Sharing the personal experience of transgender women in Malaysia - Said, Abdul Hadi (Centre for Islamisation, 2024)
This chapter explores the individual experiences of transgender women in Malaysia, emphasizing the societal obstacles and health concerns of these individuals. The definition of essential words pertaining to the lesbian, gay, bisexual, and transgender (LGBT) community is covered at the outset, giving readers a basis of understanding about this chapter. The chapter also provides insight into the experiences of transgender women as they deal with discrimination and stigma within their cultural environment. The difficulties they encounter are examined, including their financial necessity and marginalization driving their involvement in sex work. The health risks connected to these behaviors are also discussed. The document highlights the need for societal support and action to improve the quality of life and lessen their involvement in sex trafficking.